Higher Education Internationalization in Ukraine: Concerns and Hope - Sikorskaya, Irina (International Higher Education, 2017)
Internationalization is gradually becoming integrated into the core functions of Ukrainian higher education institutions. Recent developments at the international and national levels are conducive to enhancing and intensifying the process, but a number of challenges still prevent it from progressing substantially. There is a call to make a quality shift in embracing internationalization.